Nonalcoholic Fatty Liver Disease and Diabetes: An Epidemiological Perspective - Rhee, Eun-Jung (Endocrinol Metab (Seoul), 2019)
Nonalcoholic fatty liver disease (NAFLD) is thought to stem from the body's inability to store excess energy in adipocytes; as such, it is commonly viewed as the hepatic manifestation of metabolic syndrome. The pathogenesis of NAFLD involves ectopic fat accumulation, which also takes place in the liver, muscle and visceral fat. NAFLD is rapidly becoming more widespread in Korea, with an estimated prevalence of 30% in adults. Type 2 diabetes mellitus (T2DM) and NAFLD share insulin resistance as a common pathophysiological mechanism, and each of these two diseases affects the development of the other. Recent studies have suggested that NAFLD is often present as a comorbidity in T2DM patients. The mutual interrelationship between these conditions is shown by findings suggesting that T2DM can exacerbate NAFLD by promoting progression to nonalcoholic hepatosteatosis or fibrosis, while NAFLD causes the natural course of diabetic complications to worsen in T2DM patients. It remains unknown whether one disease is the cause of the other or vice versa. In this review, I would like to discuss current epidemiological data on the associations between NAFLD and T2DM, and how each disease affects the course of the other.